Factores inhibidores de la relocalización de actividades en los Distritos Industriales. El caso de la cerámica de Castellón - Molina Morales, F. Xavier; Ares Vázquez, Ángeles (Cuadernos de Estudios Empresariales, 2007)
The strategic decision of re-location means moving one activity from one location to another. The existence of one environment with high interdependences between firms and institutions, such as in industrial districts, may offer a greater resistance to relocation process. We aim to question whether this statement is true or not, that means, to what extent firms in districts relocate activities?, and in any case, which are the inhibitor factors of relocation? In order to address these questions we have analyzed the case of the ceramic tile industrial district in Castellon. Findings of the survey suggested that factors related to the social capital developed in the district may act as real inhibitor or restrictive factors for decisions of locating activities outside the district.